Politics and society: The Ukrainian crisis and the future of EU enlargement - Marijana Opashinova Shundovska (University American College Skopje, 2022)
The embryonically conceived vision for a free Europe as an inevitable premise to strengthen the modern civilization has been deeply rooted in the European unification as a powerful historical urge, deriving from the structural and irreversible crisis of European nation-states. The unification of the continent based on lasting peace, prosperity, freedom and equality have been the values agreed to be accepted and implemented by the member states and to be applied as well by all aspiring countries wishing to join the European Union. Increasing inter-state dependency justified Schuman's plan to gradually create a united continent based on practical achievements and mutual solidarity. The enlargement process, being the most successful project in history has evolved significantly over the years but managed to maintain the effect of Europeization through reform-package conditionality, in order to keep its credibility and consistency. In this joint venture journey of more than a half century, some countries entered less prepared than others, making the EU re-invent the old and introduce new models of accession that will help the countries both to enter in a better-prepared manner and enable the smooth acceptance of newcomers in the family. Recent developments in the Eastern neighborhood have challenged the "never again" promise given in the past century to confront wars as a political tool. It came as a wake-up call for the European leaders to promptly adapt the European narrative on enlargement. Considering the drastic shift particularly in the security landscape, the EU re-gained the enlargement dynamic to safeguard wider peace and stability. This paper will analyze the different stages of the EU enlargement, suggesting that despite the strict criteria for membership, this process has not always been exclusively merit-based, but also politically driven as a cause of major geostrategic importance.
Keywords: 330; enlargement; integration process; criteria for membership; political decision-making; new methodology